Clinicopathological aspects of primary mucosa‐associated lymphoid tissue lymphoma of the salivary gland: A retrospective single‐center analysis of 72 cases. (29th March 2021) - Zhang, Chunye; Xia, Ronghui; Gu, Ting; Wang, Lizhen; Tian, Zhen; Zhu, Ling; Han, Jing; Hu, Yuhua; Wang, Yu; Sun, Jingjing; Li, Jiang
Abstract: Background: Salivary gland extranodal marginal zone lymphoma of mucosa‐associated lymphoid tissue lymphoma (MALT lymphoma) is uncommon and has not been studied extensively. We aimed to investigate the features of clinicopathological and molecular changes of salivary MALT lymphoma. Methods: Seventy‐two cases of primary salivary MALT lymphoma that had clinicopathological information available were utilized in this study. MALT1 gene translocation, trisomy 3, and trisomy 18 were detected by interphase fluorescence in situ hybridization (FISH). The data were analyzed using SPSS 17.0 software package. Results: The ratio of male to female was 1:2.8, and the median age was 57.0 years. 12.5% (9/72) of the patients presented with multiple swellings. Among the others with solitary mass, the parotid gland was involved most frequently (47/63, 74.6%), followed by the palate (7/63, 11.1%). 34.7% of patients had an autoimmune disease, with Sjögren syndrome (SS) being the most common. Among the 70 cases successfully performed, it was identified that trisomy 3 was the most frequent molecular change (41/70, 58.6%), followed by trisomy 18 (7/70, 10%) and MALT1 translocation (5/70, 7.1%). The tumor tissue tended to exhibit trisomy 3 in patients without SS ( p = 0.038). The 5‐year overall survival was 94.1%, and the 5‐year disease‐free survival was 85.3% (mean follow‐up time: 104.7 months). The patients without SS and trisomy 18 had a prolonged recurrence‐free survival ( p = 0.015, p = 0.001 respectively). Conclusion: Salivary gland MALT lymphoma is associated with autoimmune diseases, and trisomy 3 is the most common genetic change. Trisomy 18 can be used to predict the possibility of tumor relapse.